Use of a Modified Intramedullary Pinning Technique for Distal Femoral Physeal Salter–Harris Type I and II Fracture Management: A Retrospective Study of 31 Cats - Bondonny, Laura; Jacqmin, Maxime; Ferrand, François-Xavier; Taroni, Mathieu; Rivier, Pablo (Veterinary and Comparative Orthopaedics and Traumatology, 2023)
Objective To report a modified intramedullary pinning technique, and associated outcomes, for distal femoral physeal Salter–Harris type I and II fracture management in cats.Study Design Retrospective study including client-owned cats presented between November 2014 and February 2022 with distal femoral physeal fractures treated with an intramedullary pin and one antirotational pin inserted in the lateral femoral condyle. Collected data included signalment, fracture characteristics according to the Salter–Harris classification, surgical data (intramedullary and antirotational pin sizes), and outcome data (radiographic and functional outcomes and complications).Results Thirty-one cats were included in this study. Bone healing was radiographically confirmed 6 to 8 weeks postoperatively in all cases. The majority of cats (30/31) were classified as full functional outcomes at mid-term follow-up. The overall mid-term complication rate was 3% (1/31). Implant migration was not observed and implant removal was not needed in any case.Conclusion The modified intramedullary pinning technique for distal femoral Salter–Harris I and II fracture management in cats was associated with an full functional outcome.
Keywords: fracture; fixation; femur; Salter–Harris; physeal fracture